Improving image contrast in fluorescence microscopy with nanostructured substrates - Brunstein, Maia (2015)
Metallic and dielectric nanostructures can show sharp contrastedresonances, sensitive to the environment, and high field enhancement insub-wavelength volumes. For this reason, these structures are commonlyused as molecular sensors. Only few works have focused on theirapplication in optical microscopy, in particular in superresolution. In thiswork we have designed, fabricated and optically tested a nanostructuredTiO2 substrate, fabricated by direct embossing of TiO2 derived film, as asubstrate for fluorescence microscopy. Moreover, using numericalsimulations, we have compared the signal to background noise with respectto other metallo-dielectric structures. We show that the TiO2 structure is agood candidate for reducing the thickness of the fluorescence excitationdown to ~100 nm. Therefore, this substrate can be used to obtain TotalInternal Reflection (TIRF) axial resolution without a TIRF-Microscopysystem.